2010
DOI: 10.1021/la101763b
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry and Spectroscopy of UG8 Asphaltene Langmuir Film, Part 1

Abstract: This research focuses on a systematic investigation of UG8 asphaltene Langmuir films at the air-water interface using toluene as the spreading solvent. From the surface pressure-area isotherms, it was concluded that small-sized aggregates are spread on the water surface and the compression of the film leads to formation of large aggregates. Our methods provide a stringent test and confirmation for the formation of corresponding asphaltene nanoaggregates that have recently been proposed for bulk solutions. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 36 publications
10
43
0
Order By: Relevance
“…Results show that based on the same mass of asphaltenes spread at the interface, the slope of the surface pressure curve (between 10 and 40 mN/m) for the first compression increases as the concentration of the spreading solution decreases. These results are in agreement with other works ,, that relate the active molecular area with the size of the asphaltene aggregate at the interface. Spreading solutions of higher concentrations provide larger asphaltene aggregates reducing their interfacial activity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Results show that based on the same mass of asphaltenes spread at the interface, the slope of the surface pressure curve (between 10 and 40 mN/m) for the first compression increases as the concentration of the spreading solution decreases. These results are in agreement with other works ,, that relate the active molecular area with the size of the asphaltene aggregate at the interface. Spreading solutions of higher concentrations provide larger asphaltene aggregates reducing their interfacial activity.…”
Section: Resultssupporting
confidence: 93%
“…Images showed that these clusters are adsorbed at the interface as a whole domain. Orbulescu et al worked with asphaltene nanoaggregates and showed, using spectroscopy techniques, that polycyclic groups tend to position parallel to interface while peripheral alkanes are perpendicular to the interface at surface coverage values close to that of a theoretical monolayer (∼20 Å 2 /molecule). Zhang et al studied the effect of the spreading solvent in asphaltene interfacial behavior during compression–expansion experiments and found that the use of toluene favors the expansion process and weakens the compressibility of asphaltene monolayers .…”
Section: Introductionmentioning
confidence: 99%
“…(10) and correlation coefficients calculated for the consecutive layers of multilayer films. accordance with the results published in the literature [38,39].…”
Section: Analysis Of the Isotherms: The Polycondensed Aromatic Compousupporting
confidence: 93%
“…It was proposed in the literature that formation of stable films at the oil-water or air-water interfaces is due to the polar aromatic ring system and apolar alkyl side chains present in asphaltenes [30,31,36,37]. However, at concentrations above 1 mg ml −1 , asphaltenes form nanoaggregates [38,39] in solution prior to spreading, or upon film compression. Due to interplay of complex steric and energetic factors, the films formed with asphaltenes are challenging for a theoretical description.…”
Section: Introductionmentioning
confidence: 99%
“…The films of asphaltene nanoaggregates are found to be ∼2 nm, whether grown from toluene or chloroform, which is in accordance with small aggregation numbers. 70,71 The size of asphaltenes and clusters has been investigated by a series of studies specifically analyzing the absolute crosssection of SAXS and SANS together. 45,46 Figure 18 shows an example of this analysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%